Levels and Determinants of Place-Of-Death Congruence in Palliative Patients: A Systematic Review - García-Sanjuán, Sofía; Fernández-Alcántara, Manuel; Clement-Carbonell, Violeta; Campos-Calderón, Concepción Petra; Orts-Beneito, Núria; Cabañero-Martínez, María José (Frontiers in Psychology, 2022)
Introduction: Congruence, understood as the agreement between the patient's preferred place of death and their actual place of death, is emerging as one of the main variables indicating the quality of end-of-life care. The aim of this research was to conduct a systematic literature review on levels and determinants of congruence in palliative patients over the period 2010–2021. Method: A systematic review of the literature in the databases of PubMed, Scopus, Web of Science, PsycINFO, CINAHL, Cuiden, the Cochrane Library, CSIC Indexes, and IBECS. Information was extracted on research characteristics, congruence, and associated factors. Results: A total of 30 studies were identified, mainly of retrospective observational design. The congruence values varied substantially between the various studies, ranging from 21 to 100%. The main predictors of congruence include illness-related factors (functional status, treatments and diagnosis), individual factors (age, gender, marital status, and end of life preferences), and environmental factors (place of residence, availability of health, and palliative care services). Conclusion: This review, in comparison with previous studies, shows that treatment-related factors such as physical pain control, marital status, having a non-working relative, age, discussing preferred place of death with a healthcare professional, and caregiver's preference have been associated with higher levels of congruence. Depending on the study, other factors have been associated with either higher or lower congruence, such as the patient's diagnosis, gender, or place of residence. This information is useful for designing interventions aimed towards greater congruence at the end of life.